Oral Pharmacokinetics of a Chitosan-Based Nano- Drug Delivery System of Interferon Alpha - Imperiale, Julieta C. (Polymers (Basel), 2019)
Interferon alpha (IFNα) is a protein drug used to treat viral infections and cancer diseases. Due to its poor stability in the gastrointestinal tract, only parenteral administration ensures bioavailability, which is associated with severe side effects. We hypothesized that the nanoencapsulation of IFNα within nanoparticles of the mucoadhesive polysaccharide chitosan would improve the oral bioavailability of this drug. In this work, we produced IFNα-loaded chitosan nanoparticles by the ionotropic gelation method. Their hydrodynamic diameter, polydispersity index and concentration were characterized by dynamic light scattering and nanoparticle tracking analysis. After confirming their good cell compatibility in Caco-2 and WISH cells, the permeability of unmodified and poly(ethylene glycol) (PEG)-modified (PEGylated) nanoparticles was measured in monoculture (Caco-2) and co-culture (Caco-2/HT29-MTX) cell monolayers. Results indicated that the nanoparticles cross the intestinal epithelium mainly by the paracellular route. Finally, the study of the oral pharmacokinetics of nanoencapsulated IFNα in BalbC mice revealed two maxima and area-under-the-curve of 56.9 pg*h/mL.